2008
DOI: 10.1159/000162679
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Dietary Intake of C18:1 Trans Fatty Acids Decreases the Function of Cellular Immunity in Healthy Young Men

Abstract: Aim: In this study, we tested the impact of short-term intake of increased amounts of C18:1 trans fatty acids (TFAs) on parameters of cellular and humoral immunity in healthy young men. Methods: Twenty-seven healthy young men were subsequently exposed to a standard diet for 7 days and an experimental TFA-enriched diet for 4 days. The mean energy content of these diets was 2,453 and 2,455 kcal/day, with 10, 35 and 55% of energy from proteins, fats and carbohydrates, respectively. Standard diet contained about 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…A diet rich in various trans -C18:1 has been shown to increase the serum levels of all TFA to between 40–120 mM [29], suggesting that the in vitro study TFA doses maybe 2–4 times higher than found in human serum. In vitro studies are limited in that higher concentrations are necessary in order to observe a biologic effect and need to be confirmed in dietary studies.…”
Section: Discussionmentioning
confidence: 95%
“…A diet rich in various trans -C18:1 has been shown to increase the serum levels of all TFA to between 40–120 mM [29], suggesting that the in vitro study TFA doses maybe 2–4 times higher than found in human serum. In vitro studies are limited in that higher concentrations are necessary in order to observe a biologic effect and need to be confirmed in dietary studies.…”
Section: Discussionmentioning
confidence: 95%
“…LA and EA are known to be risk factors for CRCs (14,2224), enhancing inflammation and suppressing mucosal immunity (2528). LA-derived prostaglandin E2, produced by cyclooxygenase-2, induces chronic persistent inflammation, which produces reactive oxygen species (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…LA-derived prostaglandin E2, produced by cyclooxygenase-2, induces chronic persistent inflammation, which produces reactive oxygen species (25,26). Likewise, EA induces secretion of TNF-α, activation of nuclear factor-κB, and inhibition of cluster of differentiation 8+ T-lymphocytes (27,28). …”
Section: Discussionmentioning
confidence: 99%